Os significados construídos por cuidadores que trabalham em uma instituição de longa permanência a respeito do cuidado ao idoso - Souza, Maria Betânea dos Santos (2014)
Introduction: The increase in the elderly has been discussion agenda specifically in the healthcare sector, noticing the deficit of human resources, especially trained, needed to meet the demands of these people. The institutional caregiver is the responsible for serving the needs of daily life of the elderly, thus should possess knowledge and skills in physical and emotional closeness relation. Objectives: To analyze the meanings constructed by institutional caregivers who works on a long-term institution regarding elderly care. To identify the profile of the study participants according to: age, marital status, gender, education, religion, time on the job and training. To describe the meaning of care given by caregivers working in an institution for the aged and to investigate how caregivers described how elderly care interferes with their physical and emotional health. Methodology: Exploratory study, descriptive, qualitative approach. Twelve caregivers participated after authorization of the institution, approval of the scientific committee, of the research ethics committee and signing the consent form. Data were collected between May and July 2012, through semi-structured interview, when was applied open questions form. The interpretation, categorization and discussion of information was obtained by the technique of content analysis and subjective information in the light of Symbolic Interaction. Results: The central theme interconnects up to five categories of analysis: Care as a stage of dependence - patronizing old age. Care as an extended family. Care as meeting the needs of daily life, mediated by affectivity. Care as a reward for the affection of those who once also has cared. Seeing limited by not being able to do more. Caregivers when interacted with the elderly built positive and negative symbols. The care includes: love, affection, attention, satisfaction and joy, but there are concerns emerging feelings of anxiety, sadness, fear, frustration and helplessness. Final Thoughts: The caregivers interacted with the elderly effectively. This condition is justified because it is a religious philanthropic institution run by the sisters of charity. Situation that can facilitate interaction and respect, preserving the interaction of the elderly in their social environment, favoring positive attention toward aging. Being a subject still little explored in the literature was limited in finding references for discussion. The results corresponded to a specific reality and should not be considered as the reality of all long-stay institutions and institutional caregivers. Considering the importance of new research covering aspects related to the training of these professionals, as well as actions related to the involvement of public health policies. Still on how human resources are organized in the institution to take care all dimensions, needs and peculiarities of that the number of elderly population, are issues that need to be investigated. It is suggested to hire more caregivers, better wages, reduced working hours and that the institutions give more opportunities to conducting training courses and update the field of gerontology.